Mesomorphism of novel stilbene-based bent-core liquid crystals. Issue 7 (28th May 2021) - Trišović, N.; Matović, L.; Tóth-Katona, T.; Saha, R.; Jákli, A.
ABSTRACT: A series of asymmetric bent-core liquid crystals, bearing the stilbene moiety in the side wing, was synthesised and characterised. Structural modifications of the non-stilbene wing resulted in formation of various mesophases. Compounds 1 and 3 with an ester linking group between the phenyl rings in this wing have an enantiotropic non-polar smectic-type mesophase, while compound 2, incorporating the biphenyl moiety, has a ferroelectric SmCa PF phase. The molecules of 2 undergo photoisomerisation in solution under UV irradiation, while the mesophases are unstable and UV irradiation leads to irreversible changes. The mesophases of 1 and 3 do not show any electro-optical switching and polarisation current. Applying low frequency AC voltage on a planarly aligned film of compound 2, smectic domains grow, while the birefringence and an image flickering increase. The observed features of these compounds identify stilbene as an attractive moiety in the design of advanced materials based on bent-core molecules. Graphical abstract: